Phospholipase C beta1 (PI-PLCbeta1)/Cyclin D3/protein kinase C (PKC) alpha signaling modulation during iron-induced oxidative stress in myelodysplastic syndromes (MDS) - Cappellini, A; Mongiorgi, S; Finelli, C; Fazio, A; Ratti, S; Marvi, MV; Curti, A; Salvestrini, V; Pellagatti, A; Billi, AM; Suh, P-G; McCubrey, JA; et al. (Federation of American Society of Experimental Biology (FASEB), 2020)
MDS are characterized by anemia and transfusion requirements. Transfused patients frequently show iron overload that negatively affects hematopoiesis. Iron chelation therapy can be effective in these MDS cases, but the molecular consequences of this treatment need to be further investigated. That is why we studied the molecular features of iron effect and Deferasirox therapy on PI-PLCbeta1 inositide signaling, using hematopoietic cells and MDS samples. At baseline, MDS patients showing a positive response after iron chelation therapy displayed higher levels of PI-PLCbeta1/Cyclin D3/PKCalpha expression. During treatment, these responder patients, as well as hematopoietic cells treated with FeCl3 and Deferasirox, showed a specific reduction of PI-PLCbeta1/Cyclin D3/PKCalpha expression, indicating that this signaling pathway is targeted by Deferasirox. The treatment was also able to specifically decrease the production of ROS. This effect correlated with a reduction of IL-1A and IL-2, as well as Akt/mTOR phosphorylation. In contrast, cells exposed only to FeCl3 and cells from MDS patients refractory to Deferasirox showed a specific increase of ROS and PI-PLCbeta1/Cyclin D3/PKCalpha expression. All in all, our data show that PI-PLCbeta1 signaling is a target for iron-induced oxidative stress and suggest that baseline PI-PLCbeta1 quantification could predict iron chelation therapy response in MDS.